Targeting the Mesolithic: Interdisciplinary approaches to archaeological prospection in the Brown Bank area, southern North Sea. (20th May 2021) - Missiaen, Tine; Fitch, Simon; Harding, Rachel; Muru, Merle; Fraser, Andy; De Clercq, Maikel; Moreno, David Garcia; Versteeg, Wim; Busschers, Freek S.; van Heteren, Sytze; Hijma, Marc P.; Reichart, Gert-Jan; et al.
Abstract: This paper describes some results of the research undertaken over the Brown Bank area during recent (2018/2019) geoarchaeological surveys in the North Sea which included seismic imaging, shallow (vibro)coring and dredging. It examines the benefits of simultaneous high-resolution (0.5 – 1 m) and ultra-high-resolution (10–20 cm) seismic survey techniques and a staged approach to resolving the submerged Holocene landscape in the highest possible detail for the purpose of targeted prospecting for archaeological material from the Mesolithic landscape of Doggerland. The materials recovered from such surveys offer significantly greater information due to an enhanced understanding of the context in which they were recovered. The importance of this information cannot be understated archaeologically, as few locations on land provide the opportunity to recover archaeological finds in situ within preserved landscapes. Moreover, it allows offshore areas of potential human activity to be prospected with some certainty of success.